Component Analysis of Oxygen Transport Resistance Increased due to Water Accumulated in a PEFC. Issue 12 (1st December 2022) - Iizuka, Yutaka; Tabe, Yutaka; Kitami, Yuki; Uemura, Suguru
Abstract : To increase the power output of polymer electrolyte fuel cells, care in the water management is important. This study extends the limiting current analysis to evaluate the effects of condensed water in the oxygen transport resistance. The resistance increase by water accumulation is separated into pressure-dependent and -independent components by introducing two indices determining the condensed water effects. The components approximately correspond to the transport resistances outside and inside of the catalyst layer (CL) respectively. The results show that both of the components increase from the low index region at 35 °C. At 80 °C, the increase in the pressure-dependent resistance is suppressed, while the pressure-independent resistance increases gradually as the current density increases. This gradual increase is confirmed in a cell with 1.0 mm wide channels, and the increase is suppressed with 0.3 mm wide channels. The observation of water distributions by a freezing method and cryo-SEM shows that there is ice at the interface between the micro-porous layer and CL only with the wider channel at 80 °C. These suggest that poorer contact of the interface under the wider channel allows condensed water to accumulate and expand at the interface, disturbing the oxygen transport to the CL.